Critical discourse analysis of ‘Peringatan Darurat Garuda Biru’ in digital political communications - Putra, Dedi Kurnia Syah; Harliantara; Damayanti, Alina Maritsa; Li, Hao (Jurnal Studi Komunikasi, 2025)
The development of digital technology has changed the landscape of political communication, especially through social media, which has now become the main arena for narrative battles and political meaning production. This study analyses the cyber politics strategy in the ‘Garuda Biru Emergency Warning’ content uploaded by the Instagram account @narasi.tv, as a form of symbolic criticism of the democratic situation in Indonesia. Using a qualitative approach with a critical paradigm, this study applies Teun A. van Dijk's Critical Discourse Analysis combined with classical propaganda theory and digital political communication theory. Data was obtained through the documentation of visual and textual content. This study seeks to answer three main questions: (1) How are political propaganda strategies constructed in the “Peringatan Darurat Garuda Biru” content through visual symbols, diction, and narrative? (2) How does this content shape public opinion and position the media as an actor resisting elite domination? (3) To what extent does social media enable a shift in the production of political discourse from the state to independent media and digital influencers? The results of the study indicate that digital propaganda in this content is constructed through a combination of visual symbols (blue Garuda), authoritative diction (emergency warning), and aesthetic narratives that evoke public emotion. This strategy shapes opinion through affective resonance and demonstrates a shift in symbolic power from the state to independent media and digital actors. This research confirms that social media is not merely a communication tool, but also an arena for ideological contestation and discourse production in contemporary democracy